High-strength heat storage carbon material, its preparation method and application, and composition for preparing high-strength heat storage carbon material

By using a composition with a high content of binder and additive, a high-strength heat storage carbon material is prepared, which solves the problem of low compressive strength of the heat storage material, and achieves the effect of high compressive strength and thermal conductivity.

CN115141607BActive Publication Date: 2025-06-17CHINA ENERGY INVESTMENT CORP LTD +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202110351610.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-06-17
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

The compressive strength of existing heat storage materials is low and it is difficult to meet high strength requirements.

Method used

Using a composition with a high content of binder and additive, high-strength heat storage carbon materials are prepared through mixing, molding, sintering and graphitization, so as to ensure that the material has a high degree of graphitization, a specific degree of orientation and a high molding density.

Benefits of technology

While maintaining high molding density and thermal conductivity, the compressive strength and thermal conductivity of heat storage carbon materials are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003002528390000131
    Figure BDA0003002528390000131
  • Figure BDA0003002528390000141
    Figure BDA0003002528390000141
Patent Text Reader

Abstract

The present invention relates to the field of heat storage materials, and discloses a high-strength heat storage carbon material, a preparation method and application thereof, and a composition for preparing the high-strength heat storage carbon material. The graphitization degree of the high-strength heat storage carbon material is ≥90%; the overall orientation degree D(x) / D(z) of the high-strength heat storage carbon material is 100 - 500; the z-plane orientation degree D(z) / E(z) of the high-strength heat storage carbon material is 2 - 30. The high-strength heat storage carbon material has a specific overall orientation degree and z-plane curvature, and the heat storage carbon material has excellent compressive strength on the premise of maintaining high molding density and thermal conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of heat storage materials, and specifically relates to a high-strength heat storage carbon material, a preparation method and application thereof, and a composition for preparing a high-strength heat storage carbon material. Background Art

[0002] CN112111310A discloses a composition for a heat storage carbon material, a heat storage carbon material and a preparation method thereof. The composition comprises an asphalt material and graphite. Among them, the asphalt material is selected from coal-based asphalt and / or coal-based modified asphalt, and the C / H of the asphalt material is 1.3-1.7, the softening point is ≥130°C, and the residual carbon rate after carbonization is ≥66%; based on the total weight of the composition for the heat storage material, the content of the asphalt material is 10-40% by weight, and the content of the graphite is 60-90% by weight. The heat storage carbon material has high thermal conductivity, compressive strength and bulk density at the same time.

[0003] CN101948675A discloses a graphite material for solar thermal power generation heat collection and energy storage and a preparation method thereof. The performance parameters of the graphite material meet: the bulk density is ≥1.75 g / cm 3 , the resistivity is ≤7.5 μΩm, the ash content is ≤0.2%, the flexural strength is ≥18.5 MPa, the elastic modulus is ≤8.8 GPa, and the thermal expansion coefficient is ≤2.0×10 -6 / °C -1 ; the graphite material has the advantages of high heat capacity, high thermal conductivity, long service life and low cost. The preparation method is: the raw materials are screened, proportioned, kneaded, aired, vibration molded, and then through roasting, impregnation, secondary roasting, graphitization, and machining to form a heat storage material for concentrating solar thermal power generation.

[0004] Existing heat storage materials are generally sintered after being molded by pressing a binder (asphalt type) and powders (graphite, petroleum coke, etc.). The amount of the binder in the raw material formula is generally between 10-40 wt%. The binder mainly plays a role in connecting the powders to form a shape, and directly affects the strength of the material. There is a risk of dropping during the installation process of the heat storage material, and it will experience low-temperature to high-temperature cycles during use, all of which require the higher the material strength, the better. Increasing the content of the binder is an effective way to improve the strength. However, due to the characteristics of asphalt materials, when the amount of the binder is too large, the melting viscosity of the system is low, and it is easy to overflow during hot pressing molding. Larger pressure cannot be used, which will reduce the molding density and lead to a decrease in thermal conductivity and strength. Summary of the Invention

[0005] The object of the present invention is to overcome the problem of low compressive strength of heat storage materials existing in the prior art, and to provide a high-strength heat storage carbon material, its preparation method and application, and a composition for preparing the high-strength heat storage carbon material. The high-strength heat storage carbon material has a specific overall orientation degree and z-plane orientation degree, and has excellent compressive strength on the premise of maintaining high molding density and thermal conductivity.

[0006] To achieve the above object, the first aspect of the present invention provides a high-strength heat storage carbon material, characterized in that the graphitization degree of the high-strength heat storage carbon material is ≥90%;

[0007] The overall orientation degree D(x) / D(z) of the high-strength heat storage carbon material is 100-500; the z-plane orientation degree D(z) / E(z) of the high-strength heat storage carbon material is 2-30;

[0008] Wherein, D(x) refers to the diffraction peak intensity of the (002) crystal plane of the x-plane perpendicular to the stress direction in the high-strength heat storage carbon material; D(z) is the diffraction peak intensity of the (002) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; E(z) is the diffraction peak intensity of the (110) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; D(x), D(z) and E(z) are all obtained through XRD testing.

[0009] The second aspect of the present invention provides a composition for preparing a high-strength heat storage carbon material, characterized in that the composition includes a heat-conducting filler, a binder and an auxiliary agent;

[0010] Based on the total weight of the composition, the amount of the heat-conducting filler is 10-50wt%, the amount of the binder is 45-80wt%, and the amount of the auxiliary agent is 3-35wt%.

[0011] The third aspect of the present invention provides a preparation method of a high-strength heat storage carbon material, characterized in that the method includes the following steps:

[0012] (1) Mixing each component in the high-strength heat storage carbon material composition to obtain a premix;

[0013] (2) Molding the premix to obtain a molded material;

[0014] (3) Sintering and optionally graphitizing the molded material in an inert atmosphere to obtain the high-strength heat storage carbon material;

[0015] Wherein, the composition includes a heat-conducting filler, a binder and an auxiliary agent;

[0016] Based on the total weight of the composition, the dosage of the heat-conducting filler is 10-50 wt%, the dosage of the binder is 45-80 wt%, and the dosage of the auxiliary agent is 3-35 wt%.

[0017] The fourth aspect of the present invention provides a high-strength heat storage carbon material prepared by the above preparation method.

[0018] The fifth aspect of the present invention provides an application of the above high-strength heat storage carbon material or the composition for preparing the high-strength heat storage carbon material in the field of solid heat storage and / or heat dissipation.

[0019] Through the above technical solutions, the high-strength heat storage carbon material provided by the present invention, its preparation method and application, and the composition for preparing the high-strength heat storage carbon material obtain the following beneficial effects:

[0020] The high-strength heat storage carbon material provided by the present invention has a high degree of graphitization, as well as specific overall orientation degree and z-plane orientation degree. Therefore, on the premise of maintaining a high molding density and thermal conductivity, the heat storage carbon material has higher compressive strength and high thermal conductivity.

[0021] In the composition for preparing the high-strength heat storage carbon material provided by the present invention, a binder far higher than the common dosage is included. By adding an auxiliary agent to achieve a high addition amount of the binder, the binder and the auxiliary agent cooperate with each other. Therefore, the prepared heat storage carbon material not only has a high molding density and thermal conductivity, but more importantly, the heat storage carbon material has high compressive strength.

[0022] The preparation method of the heat storage carbon material provided by the present invention has the effects of high thermal conductivity and high strength through the combined action of a high-content binder and an auxiliary agent.

[0023] Furthermore, in the preparation method of the heat storage carbon material provided by the present invention, before mixing the components in the heat storage carbon material composition, a pretreatment step is carried out on the heat-conducting filler and / or the auxiliary agent. Through the pretreatment, the uniform mixing of the high-content binder with graphite and the auxiliary agent can be achieved, significantly improving the agglomeration of the binder and the interfacial compatibility between the binder and graphite and / or the auxiliary agent, and further improving the molding density, thermal conductivity and compressive strength of the prepared heat storage carbon material. Detailed Embodiments

[0024] The endpoints and any values within the ranges disclosed herein are not limited to the exact ranges or values. These ranges or values should be understood to include values close to these ranges or values. For numerical ranges, between the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values, they can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein.

[0025] In the first aspect of the present invention, a high-strength heat storage carbon material is provided, characterized in that the graphitization degree of the high-strength heat storage carbon material is ≥ 90%;

[0026] The overall orientation degree D(x) / D(z) of the high-strength heat storage carbon material is 100 - 500; the z-plane orientation degree D(z) / E(z) of the high-strength heat storage carbon material is 2 - 30;

[0027] Among them, D(x) refers to the diffraction peak intensity of the (002) crystal plane of the x-plane perpendicular to the stress direction in the high-strength heat storage carbon material; D(z) is the diffraction peak intensity of the (002) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; E(z) is the diffraction peak intensity of the (110) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; D(x), D(z) and E(z) are all obtained by XRD testing.

[0028] In the present invention, the stress direction refers to the method of applying pressure during the forming process of the high-strength heat storage carbon material.

[0029] The high-strength heat storage carbon material provided by the present invention has a high graphitization degree, as well as a specific overall orientation degree and z-plane orientation degree. Therefore, the heat storage carbon material not only has a high forming density and thermal conductivity, but more importantly, the compressive strength of the heat storage carbon material is significantly increased.

[0030] In the present invention, the graphitization degree of the high-strength heat storage carbon material is measured by the XRD method.

[0031] Further, the graphitization degree of the high-strength heat storage carbon material is ≥ 95%; the overall orientation degree D(x) / D(z) of the high-strength heat storage carbon material is 150 - 400; the z-plane orientation degree D(z) / E(z) of the high-strength heat storage carbon material is 5 - 25.

[0032] According to the present invention, the tensile strength of the heat storage carbon material is 50 - 90 MPa, the thermal conductivity is 200 - 900 W / mK, and the bulk density is 1.9 - 2.2 g / cm 3 .

[0033] In the present invention, the compressive strength of the heat storage carbon material is measured according to the GBT1431 - 2019 method; the thermal conductivity is measured according to the ASTM E1461 method; the bulk density is measured according to the GB / T24528 - 2009 method.

[0034] Further, the compressive strength of the heat storage carbon material is 55 - 70 MPa, the thermal conductivity is 350 - 600 W / mK, and the bulk density is 2 - 2.2 g / cm 3 .

[0035] The second aspect of the present invention provides a composition for preparing a high-strength heat storage carbon material, characterized in that the composition comprises a heat-conducting filler, a binder, and an auxiliary agent;

[0036] Based on the total weight of the composition, the dosage of the heat-conducting filler is 10-50 wt%, the dosage of the binder is 45-80 wt%, and the dosage of the auxiliary agent is 3-35 wt%.

[0037] In the composition for preparing a high-strength heat storage carbon material provided by the present invention, a high content of binder is included and it cooperates with the auxiliary agent. The heat storage carbon material prepared therefrom not only has a high molding density and thermal conductivity, but more importantly, the heat storage carbon material has a high compressive strength.

[0038] Further preferably, based on the total weight of the composition, the dosage of the heat-conducting filler is 30-50 wt%, the dosage of the binder is 45-65 wt%, and the dosage of the auxiliary agent is 5-15 wt%.

[0039] According to the present invention, the heat-conducting filler is graphite.

[0040] Furthermore, the heat-conducting filler is graphite with a carbon content ≥ 95 wt% and a mesh number ≤ 150. In the present invention, a composition of graphite with the above structural characteristics as the heat-conducting filler, the auxiliary agent, and the binder is used to prepare a heat storage carbon material. The obtained heat storage carbon material not only has a high molding density and thermal conductivity, but more importantly, the heat storage carbon material has a high compressive strength.

[0041] Even further, the heat-conducting filler is graphite with a carbon content ≥ 98 wt% and a mesh number of 30-80.

[0042] According to the present invention, the binder is selected from pitch and / or mesophase pitch.

[0043] In the present invention, the pitch refers to other pitches except mesophase pitch. For example, the pitch is selected from at least one of coal-based pitch, coal-based modified pitch, and petroleum pitch.

[0044] According to the present invention, the softening point of the pitch ≥ 130 °C and the residual carbon rate after carbonization ≥ 60 wt%.

[0045] In the present invention, using pitch with the above softening point and residual carbon rate after carbonization as the binder can significantly improve the compressive strength of the obtained heat storage carbon material, while not reducing the molding density and thermal conductivity of the heat storage carbon material.

[0046] In the present invention, the softening point of the pitch is measured according to the ring and ball method of GBT 4507-2014 Determination of softening point of bitumen; the residual carbon rate after carbonization of the pitch is measured according to the method of ASTM D2416-(2009).

[0047] Further preferably, the softening point of the asphalt is 140 - 200 °C, and the residual carbon rate after carbonization is ≥ 65 wt%.

[0048] According to the present invention, the mesophase content of the mesophase pitch is 70 - 100 wt%, the residual carbon rate after carbonization is ≥ 70 wt%, and the softening point is 200 - 350 °C.

[0049] In the present invention, using the mesophase pitch with the above-mentioned mesophase content and residual carbon rate after carbonization as the binder can significantly improve the tensile strength of the prepared heat storage carbon material, while not reducing the molding density and thermal conductivity of the heat storage carbon material.

[0050] In the present invention, the mesophase content of the mesophase pitch is measured according to the method of GBT 38396 - 2019 Coking Asphalt Products - Determination of Mesophase Content - Optical Reflection Microanalysis Method.

[0051] Further preferably, the mesophase content of the mesophase pitch is 85 - 100 wt%, the residual carbon rate after carbonization is ≥ 75 wt%, and the softening point of the mesophase pitch is 250 - 330 °C.

[0052] According to the present invention, the additive is selected from porous materials with a bulkiness ≥ 10; the porosity of the additive is 50 - 95%, and the average pore diameter of the additive is 5 - 500 μm.

[0053] In the present invention, using the porous material with the above structural characteristics as the additive and cooperating with the binder and graphite can increase the dosage of the binder in the composition for the heat storage carbon material, and thus significantly improve the tensile strength of the heat storage carbon material without reducing the molding density and thermal conductivity of the heat storage carbon material.

[0054] In the present invention, the bulkiness of the additive refers to the value of the volume (cubic inches) occupied by 1 ounce (28.35 grams) of the material. The specific test method is as follows: Weigh 28.35 grams of the material and naturally load it into a graduated cylinder, measure the natural volume of the material as A mL, and the bulkiness B = A * 0.061; the porosity of the additive is measured by the mercury intrusion method; the average pore diameter of the additive is measured by the mercury intrusion method.

[0055] Further preferably, the bulkiness of the additive is ≥ 50, the porosity of the additive is 80 - 95%, and the average pore diameter of the additive is 50 - 200 μm

[0056] According to the present invention, the additive is selected from heat-conducting adsorbents and / or non-heat-conducting adsorbents.

[0057] According to the present invention, the heat-conducting adsorbent is selected from at least one of expanded graphite, carbon nanotubes, graphene, carbon felt, graphite foam, nano boron nitride, and nano alumina.

[0058] According to the present invention, the non-heat-conducting adsorbent is selected from at least one of activated carbon, clay, bentonite, montmorillonite, and expanded vermiculite.

[0059] The third aspect of the present invention provides a method for preparing a high-strength heat storage carbon material, which is characterized in that the method includes the following steps:

[0060] (1) Mixing the components in the high-strength heat storage carbon material composition to obtain a premix;

[0061] (2) Molding the premix to obtain a molded material;

[0062] (3) Sintering and optionally graphitizing the molded material in an inert atmosphere to obtain the high-strength heat storage carbon material;

[0063] Wherein, the composition includes a heat-conducting filler, a binder, and an auxiliary agent;

[0064] Based on the total weight of the composition, the dosage of the heat-conducting filler is 10-50 wt%, the dosage of the binder is 45-80 wt%, and the dosage of the auxiliary agent is 3-35 wt%.

[0065] In the present invention, a heat storage carbon material prepared by combining a high dosage of a binder with an auxiliary agent and a heat-conducting filler, through mixing, molding, calcination, and optional graphitization, maintains a high molding density and thermal conductivity. At the same time, the tensile strength of the heat storage carbon material is significantly improved.

[0066] According to the present invention, based on the total weight of the composition, the dosage of the heat-conducting filler is 10-50 wt%, the dosage of the binder is 45-80 wt%, and the dosage of the auxiliary agent is 3-35 wt%.

[0067] In the preparation method of the present invention, the heat-conducting filler, the binder, and the auxiliary agent are as described in the second aspect of the present invention, and will not be elaborated herein.

[0068] In the present invention, in step (1), the dry powders of the binder, graphite, and auxiliary agent are directly mixed, and the equipment used for mixing can be conventional equipment in the art, such as a three-dimensional mixer.

[0069] According to the present invention, the method further includes pre-treating the heat-conducting filler and / or the auxiliary agent.

[0070] In the present invention, through a pretreatment step for the heat-conducting filler and / or the additive, uniform mixing between a high content of binder, graphite, and the additive can be achieved through the pretreatment, significantly improving the agglomeration of the binder and the interfacial compatibility between the binder and graphite and / or the additive. Furthermore, the molding density, thermal conductivity, and compressive strength of the prepared heat storage carbon material are further improved.

[0071] According to the present invention, the method for the pretreatment includes:

[0072] (1-1) Mixing the heat-conducting filler and / or the additive with a solvent having a boiling point less than 100 °C; the amount of the solvent used is 1-10 wt% of the total weight of the heat-conducting filler and / or the additive;

[0073] Alternatively, the method for the pretreatment includes:

[0074] (1-2) Immersing the heat-conducting filler and / or the additive in an asphalt solution, filtering after immersion, and removing the solvent; the concentration of the asphalt solution is 0.1-5 wt%.

[0075] Furthermore, in step (1-1), the amount of the solvent used is 5-8 wt% of the total weight of the heat-conducting filler and / or the additive.

[0076] Furthermore, in step (1-2), the concentration of the asphalt solution is 0.5-3 wt%.

[0077] According to the present invention, in step (1-1), the solvent is selected from at least one of ethanol, tetrahydrofuran, and n-hexane.

[0078] According to the present invention, in step (1-2), the solvent in the asphalt solution is selected from at least one of tetrahydrofuran, toluene, quinoline, and heavy oil.

[0079] According to the present invention, the immersion time is 5-15 min, preferably 5-10 min.

[0080] According to the present invention, in step (2), the molding conditions include: the molding temperature is 150-600 °C, the molding pressure is 5-100 MPa, and the heat preservation and pressure holding time is 0.5-5 h.

[0081] In the present invention, molding the mixture under the above molding conditions can obtain a uniform and dense structure and the additive can be uniformly dispersed in the heat storage material. Furthermore, the prepared high-strength heat storage carbon material has high compressive strength, high thermal conductivity, and high molding density.

[0082] Further preferably, the molding conditions include: the molding temperature is 250-550 °C, the molding pressure is 10-50 MPa, and the heat preservation and pressure holding time is 2-4 h.

[0083] According to the present invention, in step (3), the sintering conditions include: the sintering temperature is 900 - 1600 °C, and the sintering isothermal time is 0.5 - 3 h.

[0084] In the present invention, the inert atmosphere is selected from nitrogen and / or argon.

[0085] In the present invention, roasting the formed sample under the above conditions can cause the binder to undergo sufficient carbonization, enabling closer bonding and higher strength between the components, and further enabling the prepared high-strength heat storage carbon material to have high compressive strength, high thermal conductivity, and high forming density.

[0086] Further preferably, the roasting conditions include: the roasting temperature is 1200 - 1600 °C, and the roasting isothermal time is 0.5 - 1 h.

[0087] In the present invention, in order to further improve the forming density, thermal conductivity, and tensile strength of the prepared high-strength heat storage carbon material, preferably, a graphitization step is further performed on the product obtained by roasting. In particular, according to the present invention, the graphitization conditions include: the graphitization temperature is 2500 - 3200 °C, and the graphitization isothermal time is 0.5 - 2 h. Performing the graphitization under the above conditions can cause the binder to undergo a graphitization transformation to become a graphite material with higher thermal conductivity, and at the same time can improve the thermal conductivity and strength, and further enable the prepared high-strength heat storage carbon material to have more excellent tensile strength, thermal conductivity, and forming density.

[0088] Further, the graphitization conditions include: the graphitization temperature is 2800 - 3200 °C, and the graphitization isothermal time is 0.5 - 1 h.

[0089] The fourth aspect of the present invention provides a high-strength heat storage carbon material prepared by the above preparation method.

[0090] In the present invention, the graphitization degree of the high-strength heat storage carbon material is ≥ 90%;

[0091] The overall orientation degree D(x) / D(z) of the high-strength heat storage carbon material is 100 - 500; the z-plane orientation degree D(z) / E(z) of the high-strength heat storage carbon material is 2 - 30;

[0092] Wherein, D(x) refers to the diffraction peak intensity of the (002) crystal plane of the x-plane perpendicular to the stress direction in the high-strength heat storage carbon material; D(z) is the diffraction peak intensity of the (002) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; E(z) is the diffraction peak intensity of the (110) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; D(x), D(z), and E(z) are all obtained through XRD testing.

[0093] In the present invention, the tensile strength of the heat storage carbon material is 50-90 MPa, the thermal conductivity is 200-900 W / mK, and the bulk density is 1.9-2.2 g / cm 3 .

[0094] The fifth aspect of the present invention provides the application of the above high-strength heat storage carbon material or the above composition for preparing a high-strength heat storage carbon material in the field of solid heat storage and / or heat dissipation.

[0095] The present invention will be described in detail below through examples. In the following examples,

[0096] The bulk density of the heat storage carbon material is measured according to the method of GB / T24528-2009;

[0097] The thermal conductivity of the heat storage carbon material is measured according to the method of ASTM E1461;

[0098] The compressive strength of the heat storage carbon material is measured according to the method of GBT1431-2019;

[0099] D(x), D(z) and E(z) of the heat storage carbon material are obtained by XRD;

[0100] The graphitization degree of the heat storage carbon material is measured by the XRD method;

[0101] The porosity and average pore diameter of the additive are measured by the mercury intrusion method;

[0102] The bulkiness of the additive is measured according to the following method:

[0103] Weigh 28.35 grams of the material, naturally load it into a graduated cylinder, measure the natural volume of the material as AmL, and the bulkiness B = A * 0.061;

[0104] The softening point of the asphalt is measured according to the method of GBT4507-2014 Asphalt Softening Point Determination Method - Ring and Ball Method;

[0105] The residual carbon rate after carbonization of the asphalt is measured according to the method of ASTM D2416-(2009);

[0106] The mesophase content of the mesophase pitch is measured according to the method of GBT 38396-2019 Coking Asphalt Products - Determination of Mesophase Content - Optical Reflection Microanalysis Method;

[0107] The raw materials used in the examples and comparative examples are all commercially available products.

[0108] Example 1

[0109] (1) 33 parts of graphite (carbon content 99.5 wt%, 50 mesh) and 7 parts of expanded graphite (porosity 85%, pore size 5 - 150 μm, bulkiness 70) were impregnated in a 1 wt% mesophase pitch (mesophase content 100 wt%, carbon residue rate 75%, softening point 280 °C) solution, with the solvent being tetrahydrofuran. After 5 min, filtration was carried out, the solvent was dried, and it was transferred to a mixer. 60 parts of mesophase pitch (mesophase content 100 wt%, carbon residue rate 75%, softening point 280 °C) were added and mixed evenly to obtain a premix.

[0110] (2) The premix was molded by hot pressing at a temperature of 550 °C, a pressure of 75 MPa, and a heat preservation and pressure holding time of 4 h. After cooling, it was taken out to obtain a molded material.

[0111] (3) The molded material was sintered in a nitrogen atmosphere at a temperature of 1200 °C for 1 h, and the product obtained above was graphitized in an argon atmosphere at a temperature of 3000 °C for 0.5 h to prepare a heat storage carbon material A1. The structure and properties of the heat storage carbon material were tested, and the test results are shown in Table 1.

[0112] Example 2

[0113] The heat storage carbon material was prepared according to the method of Example 1, except that graphitization was not carried out. Heat storage carbon material A2 was prepared. The structure and properties of the heat storage carbon material were tested, and the test results are shown in Table 1.

[0114] Example 3

[0115] The heat storage carbon material was prepared according to the method of Example 1, except that in step (1), the amount of mesophase pitch was 47 parts, the amount of graphite was 48 parts, and the amount of expanded graphite was 5 parts. Heat storage carbon material A3 was prepared. The structure and properties of the heat storage carbon material were tested, and the test results are shown in Table 1.

[0116] Example 4

[0117] The heat storage carbon material was prepared according to the method of Example 1, except that in step (1), foam graphite with a porosity of 90%, a pore size of 50 - 200 μm, and a bulkiness of 10 was used instead of the expanded graphite in Example 1. Heat storage carbon material A4 was prepared. The structure and properties of the heat storage carbon material were tested, and the test results are shown in Table 1.

[0118] Example 5

[0119] Prepare the heat storage carbon material according to the method of Example 1, except that: in step (1), the amount of mesophase pitch is 47 parts, the amount of graphite is 48 parts, and the amount of expanded graphite is 5 parts. Its porosity is 65%, the pore size is 50 - 300 μm, and the bulkiness is 10. The heat storage carbon material A5 is obtained. Test the structure and properties of the heat storage carbon material, and the test results are shown in Table 1.

[0120] Example 6

[0121] Prepare the heat storage carbon material according to the method of Example 3, except that: in step (1), coal-based pitch with a softening point of 165 °C and a residual carbon rate of 60 wt% is used instead of mesophase pitch. The heat storage carbon material A6 is obtained. Test the structure and properties of the heat storage carbon material, and the test results are shown in Table 1.

[0122] Example 7

[0123] Prepare the heat storage carbon material according to the method of Example 1, except that: in step (2), the forming temperature is 400 °C, the pressure is 75 MPa, and the heat preservation and pressure holding time is 4 h. The heat storage carbon material A7 is obtained. Test the structure and properties of the heat storage carbon material, and the test results are shown in Table 1.

[0124] Example 8

[0125] Prepare the heat storage carbon material according to the method of Example 1, except that: in step (3), the sintering temperature is 900 °C and the heat preservation time is 1 h; the graphitization temperature is 2500 °C and the heat preservation time is 0.5 h. The heat storage carbon material A8 is obtained. Test the structure and properties of the heat storage carbon material, and the test results are shown in Table 1.

[0126] Example 9

[0127] Prepare the heat storage carbon material according to the method of Example 1, except that: in step (1), graphite and expanded graphite are not pretreated and are directly mixed with mesophase pitch. The heat storage carbon material A9 is obtained. Test the structure and properties of the heat storage carbon material, and the test results are shown in Table 1.

[0128] Comparative Example 1

[0129] Prepare the heat storage carbon material according to the method of Example 1, except that: it does not contain the additive expanded graphite. The heat storage carbon material D1 is obtained, and during the hot pressing forming process, molten pitch leaks. Test the structure and properties of the heat storage carbon material, and the test results are shown in Table 1.

[0130] The compressive strength is 15 MPa, the thermal conductivity is 150 W / mK, the bulk density is 1.5 g / cm 3 , and the graphitization degree is 93%.

[0131] Comparative Example 2

[0132] The heat storage carbon material was prepared according to the method of Example 1, except that: the amount of mesophase pitch was 90 parts, the amount of graphite was 8 parts, and the amount of expanded graphite was 2 parts. The heat storage carbon material D2 was prepared. Due to the excessive amount of the binder mesophase pitch and the insufficient amount of the additives, the forming effect was poor. The structure and properties of the heat storage carbon material were tested, and the test results are shown in Table 1.

[0133] Table 1

[0134]

[0135]

[0136] It can be seen from the results in Table 1 that the heat storage carbon material provided by the embodiment of the present invention has a high graphitization degree, and has an appropriate overall orientation degree and z-plane orientation degree, and has higher compressive strength, thermal conductivity and bulk density than the heat storage carbon material provided by the comparative example.

[0137] Furthermore, using mesophase pitch with a high residual carbon rate, or pre-treating the binder and additives, or increasing the forming temperature can further improve the compressive strength, thermal conductivity and bulk density of the heat storage carbon material.

[0138] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.

Claims

1. A composition of a high-strength heat storage carbon material, characterized in that, The composition includes a thermal conductive filler, a binder, and an additive; Based on the total weight of the composition, the dosage of the thermal conductive filler is 10 - 50 wt%, the dosage of the binder is 45 - 80 wt%, and the dosage of the additive is 3 - 35 wt%; the additive is selected from porous materials with a bulkiness ≥ 10, the porosity of the additive is 50 - 95%, and the average pore diameter of the additive is 5 - 500 μm; The thermal conductive filler is graphite; The binder is selected from pitch and / or mesophase pitch; The additive is selected from thermal conductive adsorbents and / or non-thermal conductive adsorbents. The thermal conductive adsorbents are selected from at least one of expanded graphite, carbon nanotubes, graphene, carbon felt, foam graphite, nano boron nitride, and nano aluminum nitride. The non-thermal conductive adsorbents are selected from at least one of activated carbon, clay, bentonite, montmorillonite, nano calcium silicate, and expanded vermiculite.

2. The composition according to claim 1, wherein, Based on the total weight of the composition, the dosage of the thermal conductive filler is 30 - 50 wt%, the dosage of the binder is 45 - 65 wt%, and the dosage of the additive is 5 - 15 wt%.

3. The composition according to claim 1, wherein, The thermal conductive filler is graphite with a carbon content ≥ 95 wt% and a mesh number ≤ 150.

4. The composition according to claim 1, wherein, The pitch is selected from at least one of coal-based pitch, coal-based modified pitch, and petroleum pitch.

5. The composition according to claim 1, wherein, The softening point of the pitch ≥ 130 °C, and the residual carbon rate after carbonization ≥ 60 wt%.

6. The composition according to claim 1, wherein, The mesophase content of the mesophase pitch is 70 - 100 wt%, the residual carbon rate after carbonization ≥ 70 wt%, and the softening point is 200 - 350 °C.

7. A method for preparing a high-strength heat storage carbon material from the high-strength heat storage carbon material composition according to any one of claims 1-6, wherein, The method includes the following steps: (1) Mix the components in the high-strength heat storage carbon material composition to obtain a premix; (2) Mold the premix to obtain a molded material; (3) Sinter and optionally graphitize the molded material in an inert atmosphere to obtain the high-strength heat storage carbon material; wherein the composition includes a thermal conductive filler, a binder, and an additive; Based on the total weight of the composition, the dosage of the thermal conductive filler is 10 - 50 wt%, the dosage of the binder is 45 - 80 wt%, and the dosage of the additive is 3 - 35 wt%; the additive is selected from porous materials with a bulkiness ≥ 10; the porosity of the additive is 50 - 95%, and the pore diameter of the additive is 5 - 500 μm; The thermal conductive filler is graphite; The binder is selected from pitch and / or mesophase pitch; The additive is selected from thermal conductive adsorbents and / or non-thermal conductive adsorbents. The thermal conductive adsorbents are selected from at least one of expanded graphite, carbon nanotubes, graphene, carbon felt, foam graphite, nano boron nitride, and nano aluminum nitride. The non-thermal conductive adsorbents are selected from at least one of activated carbon, clay, bentonite, montmorillonite, nano calcium silicate, and expanded vermiculite.

8. The method according to claim 7, wherein, Based on the total weight of the composition, the dosage of the thermal conductive filler is 30 - 50 wt%, the dosage of the binder is 45 - 65 wt%, and the dosage of the additive is 5 - 15 wt%.

9. The method according to claim 7, wherein, The thermal conductive filler is graphite with a carbon content ≥ 95 wt% and a mesh number ≤ 150.

10. The method according to claim 7, wherein, The pitch is selected from at least one of coal-based pitch, coal-based modified pitch, and petroleum pitch.

11. The method according to claim 7, wherein, The softening point of the asphalt is ≥130 °C, and the residual carbon rate after carbonization is ≥60 wt%.

12. The method according to claim 7, wherein, The mesophase content of the mesophase pitch is 70-100 wt%, the residual carbon rate after carbonization is ≥70 wt%, and the softening point is 200-350 °C.

13. The method according to claim 7, wherein, The method further includes pre-treating the heat-conducting filler and / or the additive.

14. The method according to claim 13, wherein, The method of the pre-treatment includes: (1-1) Mixing the heat-conducting filler and / or the additive with a solvent having a boiling point less than 100 °C; the dosage of the solvent is 1-10 wt% of the total weight of the heat-conducting filler and / or the additive; Alternatively, the method of the pre-treatment includes: (1-2) Immersing the heat-conducting filler and / or the additive in an asphalt solution, filtering after immersion, and removing the solvent, and the concentration of the asphalt solution is 0.1-5 wt%.

15. The method according to claim 14, wherein, In step (1-1), the solvent is selected from at least one of ethanol, tetrahydrofuran, and n-hexane.

16. The method according to claim 14, wherein, In step (1-2), the solvent in the asphalt solution is selected from at least one of tetrahydrofuran, toluene, quinoline, and heavy oil.

17. The method according to claim 14, wherein, The time of the immersion is 5-15 min.

18. The method according to claim 7, wherein, In step (2), the conditions for forming include: the forming temperature is 150-600 °C, the forming pressure is 5-100 MPa, and the heat preservation and pressure holding time is 0.5-5 h.

19. The method according to claim 7, wherein, In step (3), the conditions for sintering include: the sintering temperature is 900-1600 °C, and the sintering constant temperature time is 0.5-3 h.

20. The method according to claim 7, wherein, The conditions for graphitization include: the graphitization temperature is 2500-3200 °C, and the graphitization constant temperature time is 0.5-2 h.

21. A high-strength heat storage carbon material prepared by the method according to any one of claims 7-20; The graphitization degree of the high-strength heat storage carbon material is ≥90%; The overall orientation degree D(x) / D(z) of the high-strength heat storage carbon material is 100-500; the z-plane orientation degree D(z) / E(z) of the high-strength heat storage carbon material is 2-30; Wherein, D(x) refers to the diffraction peak intensity of the (002) crystal plane of the x-plane perpendicular to the stress direction in the high-strength heat storage carbon material; D(z) is the diffraction peak intensity of the (002) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; E(z) is the diffraction peak intensity of the (110) crystal plane of the z-plane parallel to the stress direction in the high-strength heat storage carbon material; D(x), D(z), and E(z) are all obtained by XRD testing.

22. The high-strength heat storage carbon material according to claim 21, wherein, The compressive strength of the heat storage carbon material is 50 - 90 MPa, the thermal conductivity is 200 - 900 W / mK, and the bulk density is 1.9 - 2.2 g / cm 3 .

23. Use of the high-strength heat storage carbon material according to claim 21 or 22 or the high-strength heat storage carbon material composition according to any one of claims 7-20 in the field of solid heat storage and / or heat dissipation.

Citation Information

Patent Citations

  • Heat accumulation and energy storage graphite material for solar thermal power generation and preparation method thereof

    CN101948675A

  • Composition for heat storage carbon material, heat storage carbon material and preparation method thereof

    CN112111310A

  • Graphite block material with ultrahigh heat conductivity and high strength and preparation method of graphite block material

    CN110550955A